Intensive smoking cessation treatment as an adjunct to concurrent psychotherapy: study protocol for a randomized controlled trial - Esra Teresa Sünkel; Alla Machulska; Marie Neubert; Tim Klucken (Trials, 2025)
Abstract Background Tobacco use is globally recognized by the World Health Organization as the foremost risk factor for premature mortality. Individuals with mental disorders exhibit a notably heightened dependence on tobacco, approximately twice as high as that of the general population. The long-term effects of nicotine consumption include an exacerbation of depressive symptoms and a decline in mental health, which can be considered additional risk factors for the vulnerable population of smokers with preexisting mental disorders. Successful smoking cessation is associated with an increase in mental health, comparable or superior to that of pharmacological antidepressant treatments. However, smoking is frequently disregarded within the realm of psychotherapeutic care, unlike in the treatment of other substance use disorders. Smoking may hinder patients’ recovery and responsiveness to psychotherapy, potentially distorting improvements in symptom severity or negative affect. Integrating smoking cessation initiatives into standard psychotherapeutic interventions thus holds significant potential and may be considered essential for long-term mental health. The current study’s objective is to assess the potential of a guideline-based smoking cessation intervention within an outpatient psychotherapeutic setting concerning changes in smoking intensity, nicotine dependence, and mental health outcomes among patients with a mental disorder adjunct to concurrent psychotherapy. This trial aims to bridge the gap between the state of research in light of evidence of the positive effects of successful smoking cessation and the actual practical provision of care in Germany. Methods The effects of an intensified smoking cessation intervention versus a treatment-as-usual (TAU) control intervention on smokers’ smoking intensity, nicotine dependence, and mental health symptoms related to a primary mental disorder will be examined in a single-center randomized controlled trial in an outpatient psychotherapeutic clinic using variance analysis methods. In this case, TAU is referred to as regular psychotherapy sessions without any additional smoking cessation treatment. The smoking intervention consists of a common guideline-based cognitive-behavioral program supplemented by a digital health application. Secondary outcomes include patients’ motivation to quit, self-efficacy, and attitudes toward online interventions. Potential moderators or mediators will be investigated in exploratory analyses. Discussion This study aims to elucidate the potential benefits of integrating smoking cessation interventions into standard psychotherapeutic treatment, akin to approaches used for other substance use disorders. While existing research highlights the positive impact of smoking cessation on mental health, its practical implications within the field of psychotherapy remain unclear. To address this gap, the current study examines the effectiveness of an intensive smoking cessation program alongside ongoing psychotherapy, focusing on both smoking status and mental health outcomes. By doing so, we aim to provide practical insights for psychotherapeutic providers regarding the integration of smoking cessation into comprehensive mental health care. Trial registration Prospectively registered on ISCRTN on 01.05.2024, reference number ISRCTN12859609.